Social Networking Spaces: From Facebook to Twitter and Everything In Between - Kelsey, Todd (Apress, 2013)
This book is a how-to guide, a tour of social networks like Facebook, Twitter, Blogger, LinkedIn, and others. It’s appropriate for beginners and anyone else who’d like to get a sense of what you can do on various social networks. I’ve tried to make the book as friendly as possible and easy to read, and I hope you enjoy it. Most of the book contains step-by-step instructions for specific things you can try. My goal is that by the end of the book, you gain a good understanding of what you can do in today’s social networks. There are also some sections written in a blog style, where I share personal examples as an attempt to provide some inspiration. I hope that when you see what I share, maybe you’ll think back to kindergarten and how much fun show-and-tell can be.